Case Report: Severe Osteoporosis and Preventive Therapy in RNA Polymerase III-Related Leukodystrophy - Furukawa, Soma; Kunii, Misako; Doi, Hiroshi; Kondo, Naohide; Ogura, Aya; Hirabuki, Koichi; Itoh, Takayuki; Matsumoto, Naomichi; Tanaka, Fumiaki; Katsuno, Masahisa; Ito, Yasuhiro (Frontiers in Neurology, 2021)
RNA polymerase III (POLR3)-related leukodystrophy is an autosomal recessive form of leukodystrophy caused by homozygous or compound heterozygous mutations of the RNA polymerase III subunit genes including subunit A (POLR3A). With respect to the manifestation triad, hypomyelination, hypodontia and hypogonadotropic hypogonadism, it is also known as 4H leukodystrophy. Here, we report a 41-year-old woman of POLR3-related leukodystrophy by carrying compound heterozygous pathogenic variants of c.2554A>G (p.M852V) and c.2668G>T (p.V890F) in the POLR3A gene. She was amenorrheic and confined to a wheelchair from the age of 15 and suffered from multiple episodes of pathologic fractures, starting with a subtrochanteric fracture of the right femur after a tonic seizure at age 30. Head MRI demonstrated hypomyelination, and atrophies of the cerebellum, brainstem and corpus callosum. Laboratory examination revealed a marked decrease of gonadotropins and estrogen, low bone density and high bone resorption markers. Administration of anti-RANKL monoclonal antibody, restored bone resorption markers to a normal level and prevented further pathological bone fractures. Our case emphasizes that osteoporosis should be recognized as a potential but serious complication in POLR3-related leukodystrophy. It may be feasible to prevent pathologic fractures by intensive osteoporosis therapy following endocrinological examinations and evaluation of bone metabolism.